The Efficacy of Information Policy: A Review of Archon Fung, Mary Graham, and David Weil's Full Disclosure: The Perils and Promise of Transparency - Winston, Clifford (Journal of Economic Literature, 2008)
The economics of information has identified an important role for government to correct situations where competition is not sufficient to reveal valuable information to consumers. Archon Fung, Mary Graham, and David Weil's Full Disclosure: The Perils and Promise of Transparency provides a thorough discussion of government-mandated disclosure policies. I use their book to frame an empirical assessment of whether these—and other information policies—have significantly reduced the costs to consumers created by imperfect information. My conclusion, which calls for more research, is that government information policies have amounted to weak solutions in search of a problem.